Institutional and Technological Foundations of Managing Spiritual Processes - Oripov Shukhratjon (Scientific Trends, 2026)
This article examines the institutional and technological foundations of managing spiritual processes in society. Spiritual processes are interpreted as a complex social phenomenon associated with the formation of social consciousness, value systems, and moral norms. The study highlights the role of state and public institutions as well as the impact of modern technologies in the context of informatization and digital transformation. It argues that effective management of spiritual processes requires harmonizing technological efficiency with humanistic values and moral responsibility. The article concludes that institutional stability and technological coherence are essential conditions for creating a healthy spiritual environment in society.
Keywords: Spiritual processes, management, institutional foundations, technological foundations, social consciousness, digital transformation, spiritual environment.